Mesoporous Strontium-Doped Phosphate-Based Sol-Gel Glasses for Biomedical Applications - Foroutan, Farzad; Kyffin, Benjamin Alexander; Abrahams, Isaac; Knowles, Jonathan C.; Sogne, Elisa; Falqui, Andrea; Carta, Daniela (Frontiers in Chemistry, 2020)
Mesoporous phosphate-based glasses have great potential as biomedical materials being able to simultaneously induce tissue regeneration and controlled release of therapeutic molecules. In the present study, a series of mesoporous phosphate-based glasses in the P2O5-CaO-Na2O system doped with 1, 3, and 5 mol % of Sr2+ were prepared using the sol-gel method combined with supramolecular templating. A sample without strontium addition was prepared for comparison. The non-ionic triblock copolymer EO20PO70EO20 (P123) was used as a templating agent. SEM images revealed that all synthesized glasses have an extended porous structure. This was confirmed by N2 adsorption-desorption analysis at 77 K that shows a porosity typical of mesoporous materials. 31P magic angle spinning nuclear magnetic resonance (31P MAS-NMR) and Fourier transform infrared (FTIR) spectroscopies have shown that the glasses are mainly formed by Q1 and Q2 phosphate groups. Degradation of the glasses in deionized water assessed over a 7-day period shows that phosphate, Ca2+, Na+ and Sr2+ ions can be released in a controlled matter over time. In particular, a direct correlation between strontium content and degradation rate was observed. This study shows that Sr-doped mesoporous phosphate-based glasses have great potential in bone tissue regeneration as materials for controlled delivery of therapeutic ions.